Evaluation of the DGE Quality Standard for the Catering in stationary Senior Facilities - Kiesswetter, Eva; Burger, Carina; Volkert, Dorothee; Arens-Azevedo, Ulrike; Alber, Rowena; Pfannes, Ulrike (Ernährungsumschau, 2016)

Size matters! Differences in nutritional care between small, medium and large nursing homes in Germany - Burger, Carina; Kiesswetter, Eva; Gietl, Angela; Pfannes, U.; Arens-Azevedo, U.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2017)
The aim of this study is to comprehensively describe nutritional care in German nursing homes (NHs) and to examine if nutritional care differs between small, medium and large NHs.Nationwide cross-sectional postal survey.Nursing homes.541 NHs across Germany.Information on structural NH characteristics and nutritional care (food provision and menu planning, nursing care, and management and quality assurance) was collected by means of a questionnaire addressed to the management of a random sample of German NHs. NHs were grouped by size as small (ae 50 beds), medium (50 - 100 beds) or large (> 100 beds) institutions. Frequencies were used to describe nutritional care, and Chi(2)-test to identify differences in nutritional care by NH size.Aspects in the domain of food provision and menu planning regarding food variety and choice were widely implemented in German NHs (77 - 100 %). Best results were achieved in the domain of nursing care, where all aspects were implemented in at least 68 % of the NHs. Aspects regarding management and quality assurance, especially those concerning staffing, i.e. the availability of an interface manager (14 %), an interdisciplinary nutrition team (12 %) and a dietician (42 %), were only rarely implemented. Differences by NH size were found between small and medium or large NHs. On the one hand, small NHs stated more often to consider individual capabilities of the residents with texture-modified food (81 % vs. 60 %, p < 0.05) and produce more often hot meals at ward level on a regular base (46 % vs. 32 %, p < 0.05) than large NHs. On the other hand, several aspects regarding food provision and menu planning, and management and quality assurance were significantly more often implemented in larger than smaller NHs.Whereas kitchen and nursing-related aspects of nutritional care seem to be widely implemented in German NHs, management and quality assurance demands are often not met. The differences found by NH size support the hypothesis that the number of residents living in a NH has an impact on how nutritional care is performed.
Keywords: Nursing home; nutritional care; nursing home size; foodservice

Texture modified diet in German nursing homes: availability, best practices and association with nursing home characteristics - Burger, Carina; Kiesswetter, Eva; Alber, Rowena; Pfannes, Ulrike; Arens-Azevedo, Ulrike; Volkert, Dorothee (BMC Geriatrics, 2019)
BACKGROUND: For nursing home (NH) residents with swallowing or chewing problems, appealing texture-modified-diets (TMD) need to be available in order to support adequate nutrition. The aim of this study was to describe the availability of TMD and best practices for TMD in German NHs and to identify related NH characteristics. METHODS: Information on NH characteristics, available texture-modified (TM)-levels (soft, "minced & moist", pureed) and implemented best practices for TMD (derived from menu plan, separately visible components, re-shaped components, considering individual capabilities of the resident) was collected in a survey in German NHs. The number of TM-levels as well as the number of best practices for TMD were tested for their association with 4 structural, 16 operational and 3 resident-related NH characteristics. RESULTS: The response rate was 7.2% (n = 590) and 563 NHs were included. The vast majority of NHs (95.2%) reported offering "minced & moist" texture and 84.2% preparing separately visible meal components. Several operational characteristics were more frequently (p < 0.05) reported from NHs offering three TM-levels (27.7%) or four best practices for TMD (13.0%) compared to NHs offering one TM-level (28.4%) or one best practice for TMD (20.1%): special diets and delivery forms (e.g. fingerfood 71.2% vs 38.8%; 80.8% vs. 44.3%), written recipes (69.9% vs. 53.1%; 68.5% vs. 53.9%), a dietetic counseling service (85.9% vs. 66.3%; 89.0% vs. 65.2%), a quality circle for nutritional care (66.7% vs. 43.8%; 71.2% vs. 50.4%), regular staff training (89.7% vs. 73.1%; 95.9% vs. 74.8%) and process instructions (73.7% vs. 53.1%; 75.3% vs. 47.8%). No associations were found regarding structural and resident-related NH characteristics, except a higher percentage of residents receiving TMD in NHs with three compared to one TM-level (median 16.3% vs. 13.2%, p = 0.037). CONCLUSION: All participating NHs offer some form of TMD, but only a small number offers a selection of TMD and pays adequate attention to its preparation. Operational NH characteristics - which might reflect a general nutritional awareness of the NH - seem to be pivotal for provision of TMD, whereas neither structural nor resident-related characteristics seem to play a role in this regard.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Chewing problems; Nursing home; Nutritional care; Swallowing problems; Texture modified diet

The Catering Situation in Institutions for Older People Results of qualitative Interviews in Institutions with and without DGE-Quality Certification - Pfannes, Ulrike; Alber, Rowena; Arens-Azevedo, Ulrike; Volkert, Dorothee; Burger, Carina; Kiesswetter, Eva (Ernährungsumschau, 2018)